JAJA WACHUKWU, 1918-1996: THE FIRST NIGERIAN MINISTER FOR FOREIGN AFFAIRS AND HIS CONTRIBUTIONS TO NIGERIA’S FOREIGN POLICY - ATAH PINE (International Studies Journal)
The paper examines the contribution of Jaja Wachukwu, the First Nigerian Minister for Foreign Affairs and his contributions to Nigeria’s Foreign Policy. The paper is situated against thebackground of the prominent role he played as the Nigeria foreign affairs Minister which however has not gone unrecognized. Thus, as a foreign affairs minister, Nigerian foreign policy was characterized by a focus on Africa as a regional power and by attachment to several fundamental principles: African unity and Afrocentrism; capability to exercise hegemonic influence in the region: peaceful settlement of disputes; non-alignment and non-intentional interference in the internal affairs of other nations; and regional economic cooperation and development. Through his excellent contribution Nigeria gained considerable fame and respect in the international system. Wachuku, gave a more credible and emphatic attention to the concept of Afrocentric and good neighborliness. For him, any Nigeria’s foreign policy that does not connote the interest of the common man in the continent of Africa is unrealistic. The paper concluded that Jaja Wachuku and his roles as the first foreign affairs Minister cannot be overemphasized. Jaja may have passed away about two decades ago, but his contributions to Nigeria's foreign policy remain a big game-changer in Nigeria’s history. The paper is however divided into four sections, the first being the breakdown of the work, followed by the introduction, his biography, and the last section deals extensively with his contributions to Nigeria's foreign policy.